Multiple congenital urogenital abnormalities in a Tennessee Walking Horse colt - Waldridge, B. M.; Lenz, S. D.; Hudson, J.; Rodríguez Hurtado, Isabel (My University, 2009)
A 9-month-old, Tennessee Walking Horse colt was examined for urinary incontinence. Cystoscopy revealed a single identifiable ureter that appeared abnormal, and sabulous urolithiasis. Only the left kidney, which appeared lobulated and hydronephrotic, could be located using ultrasound. Results of serum chemistries were consistent with renal failure. Necropsy revealed unilateral agenesis of the right kidney and ureter with severe left ureterolithiasis, bilateral cryptorchidism and segmental aplasia of the ductus deferens. Histopathological examination revealed cystitis and diffuse interstitial fibrosis of the left kidney. Congenital malformations should be included as differential diagnoses for urinary incontinence and urogenital disease. Ultrasonography and cystoscopy can be useful to diagnose suspected agenesis of the urinary system in adult horses.